PERAN KEPALA SKOLAH DALAM MENINGKATKAN KINER JA GURU MA NURUL BAHRI KABILA BONE - Masaguni, Octaviani Suryaningsih; Alamri, Moh. Rafli; Malik, Pipit; Rozza, Fahrul; Abdul, Fatra D.; Adam, Fitra Diva S.; Lahale, Silvianti (Universitas Bina Taruna Gorontalo, 2025)
This research aims to identify the principal's role in improving teacher performance. As well as analysing the principal's role in establishing communication and good relations with teachers to create a harmonious and collaborative work culture. The method used in this research is qualitative with a descriptive approach through observation, interviews, and documentation studies. The results showed that transformational-based principal leadership was able to significantly improve teacher performance. Teachers become more motivated to improve their competence, use innovative learning methods, and are more active in continuous professional development. This improvement in teacher performance directly impacts on the quality of more effective learning and improved student achievement. Therefore, it can be concluded that acting principals can play a very strategic role in developing the quality of education personnel to realise more optimal educational goals.